Gut microbiota and eye diseases: a bibliometric study and visualization analysis - Fu, Xiangyu; Tan, Haishan; Huang, Ling; Chen, Wenyue; Ren, Xiang; Chen, Danian (Frontiers in Cellular and Infection Microbiology, 2023)
The role of gut microbiota in various eye diseases has been widely reported. We used CiteSpace and VOSviewer to analyze the Web of Science Core Collection publications and establish visualization maps to show the research progress in this field. A total of 284 relevant publications were identified from 2009 to 2023. The number of studies has been small in the first five years and has grown steadily since 2016. These studies were completed by 1,376 authors from 41 countries worldwide, with the United States in the lead. Lin P has published the most papers while Horai R is the most co-cited author. The top journal and co-cited journal are both Investigative Ophthalmology & Visual Science. In the keyword co-occurrence network, except gut microbiota, inflammation becomes the keyword with the highest frequency. Co-citation analyses reveal that gut dysbiosis is involved in common immune- and inflammation-mediated eye diseases, including uveitis, diabetic retinopathy, age-related macular degeneration, dry eye, and Graves' orbitopathy, and the study of microbiomes is no longer limited to the bacterial populations. Therapeutic strategies that target the gut microbiota, such as probiotics, healthy diet patterns, and fecal microbial transplantation, are effective and critical to future research. In conclusion, the bibliometric analysis displays the research hotspots and developmental directions of the involvement of gut microbiota in the pathogenesis and treatment of some ocular diseases. It provides an overview of this field's dynamic evolution and structural relationships.